(untitled) (Texas Journal of Agriculture and Biological Sciences, 2025)
The article examines the results of research on the ecological characteristics of fish parasites of the Turtkul pond farm in the conditions of the Southern Aral Sea region. It has been established that over 40 years, the parasitofauna of individual fish has significantly depleted in the lower reaches of the Amu Darya, particularly in the Turtkul pond farm system